Be an athlete, student, and child: Portraying the mental toughness of student athletes in a religious-based middle school - Nurismawan, Ach. Sudrajad; Ramli, M.; Lestary, Yunita Dinda; Juniawan, Azka Ramadhani (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
Compared to student-athletes who attend special sports schools, those enrolled in public or religious schools tend to face greater obstacles, particularly in terms of mentoring and facilities. This phenomenological research aims to portray the mental toughness of student-athletes and their strategies for balancing their roles as athletes, students, and children while attending Middle School Muhammadiyah 12 GKB Gresik. Using semi-structured interviews with four student-athletes-selected based on the uniqueness of their sport and their willingness to participate: the researchers found that these student-athletes demonstrated good and mature mental toughness, as they were able to persevere and find solutions when facing obstacles and psychological pressures from training, competing, participating in school learning, and taking time to interact with family members at home. However, the school still needs to provide psychological support to further strengthen mental toughness through self-awareness training, imagery, and self-talk at least once per semester. The findings of this study can help fill the gap in field data on student-athletes in religious-based junior high schools in Indonesia and may inspire Islamic junior high school management to consider accepting student-athletes.